Different effects of cGMP and cAMP in the intestine of the European eel, Anguilla anguilla - TRISCHITTA, Francesca Ross; DENARO, Maria Gabr.; FAGGIO, Caterina; MANDOLFINO M; SCHETTINO T. (1996)
The regulation of salt absorption in the sea water eel intestine was studied by evaluating the effects of theophylline, 8 Br cyclic adenosine monophosphate, 8 Br cyclic guanosine monophosphate, atriopeptin III, porcine vasoactive intestinal peptide and prostaglandin E1 on the short-circuit current, the transepithelial voltage difference and conductance and on the dilution potentials. It was shown that theophylline increased the transepithelial conductance and reduced the magnitude of the dilution potentials, indicating that the drug increases the anion conductance of the tight junctions. In addition its inhibitory effect on short-circuit current and transepithelial voltage difference suggests that theophylline also affects the transcellular transport mechanisms. It was shown that 8 Br cyclic guanosine monophosphate and 8 Br cyclic adenosine monophosphate affect transcellular mechanisms underlying C1- transport since both compounds reduced short-circuit current and transepithelial voltage difference; however, cyclic adenosine monophosphate is less effective since unlike cyclic guanosine monophosphate, even at maximal concentration, it was not able to completely abolish transepithelial voltage difference and short-circuit current. The effects of cyclic guanosine monophosphate and cyclic adenosine monophosphate were not additive even if cyclic guanosine monophosphate may produce further inhibition of ion transport in 8 Br cyclic adenosine monophosphate-treated tissues. In addition, cyclic guanosine monophosphate but not cyclic adenosine monophosphate reduced the magnitude of the dilution potentials, suggesting that cyclic guanosine monophosphate acts also on the paracellular pathway. Rat atriopeptin III, a peptide known to increase cyclic guanosine monophosphate cellular levels, behaved like 8 Br cyclic guanosine monophosphate since it lowered the dilution potentials and reduced short-circuit current and transepithelial voltage difference to near zero values, suggesting that the hormone modulates both paracellular ...